Brain Networks Underlying Eye’s Pupil Dynamics - DiNuzzo, Mauro; Mascali, Daniele; Moraschi, Marta; Bussu, Giorgia; Maugeri, Laura; Mangini, Fabio; Fratini, Michela; Giove, Federico (Frontiers in Neuroscience, 2019)
Phasic changes in eye’s pupil diameter have been repeatedly observed during cognitive, emotional and behavioral activity in mammals. Although pupil diameter is known to be associated with noradrenergic firing in the pontine Locus Coeruleus (LC), thus far the causal chain coupling spontaneous pupil dynamics to specific cortical brain networks remains unknown. In the present study, we acquired steady-state blood oxygenation level-dependent (BOLD) functional magnetic resonance imaging (fMRI) data combined with eye-tracking pupillometry from fifteen healthy subjects that were trained to maintain a constant attentional load. Regression analysis revealed widespread visual and sensorimotor BOLD-fMRI deactivations correlated with pupil diameter. Furthermore, we found BOLD-fMRI activations correlated with pupil diameter change rate within a set of brain regions known to be implicated in selective attention, salience, error-detection and decision-making. These regions included LC, thalamus, posterior cingulate cortex, dorsal anterior cingulate and paracingulate cortex, orbitofrontal cortex and right anterior insular cortex. Granger-causality analysis performed on these regions yielded a complex pattern of interdependence, wherein LC and pupil dynamics were far apart in the network and separated by several cortical stages. Functional connectivity analysis revealed the ubiquitous presence of the superior frontal gyrus in the networks identified by the brain regions correlated to the pupil diameter change rate. No significant correlations were observed between pupil dynamics, regional activation and behavioral performance. Based on the involved brain regions, we speculate that pupil dynamics is implicated in changes between self- and environment-directed awareness.